2022
DOI: 10.3390/ijms23020608
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise and Activity-Based Physical Therapy on Bone after Spinal Cord Injury

Abstract: Spinal cord injury (SCI) produces paralysis and a unique form of neurogenic disuse osteoporosis that dramatically increases fracture risk at the distal femur and proximal tibia. This bone loss is driven by heightened bone resorption and near-absent bone formation during the acute post-SCI recovery phase and by a more traditional high-turnover osteopenia that emerges more chronically, which is likely influenced by the continual neural impairment and musculoskeletal unloading. These observations have stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 141 publications
(319 reference statements)
0
27
0
Order By: Relevance
“…OPG is produced in response to different stimuli and is responsible for orchestrating bone remodelling in osteoblast cells [50,51]. After the electrical stimulation, we did not observe changes in the mRNA levels, but we believe that it would be convenient in future studies to determine the RANKL values to verify the RANKL/OPG ratio, responsible for bone remodelling.…”
Section: Electrical Stimulation Enhances Proliferation and Differenti...mentioning
confidence: 75%
See 1 more Smart Citation
“…OPG is produced in response to different stimuli and is responsible for orchestrating bone remodelling in osteoblast cells [50,51]. After the electrical stimulation, we did not observe changes in the mRNA levels, but we believe that it would be convenient in future studies to determine the RANKL values to verify the RANKL/OPG ratio, responsible for bone remodelling.…”
Section: Electrical Stimulation Enhances Proliferation and Differenti...mentioning
confidence: 75%
“…Lower threshold sensitivities to alignment with the applied EF were observed in N2a at [0. 35,50] mV/mm, as well as the proliferation of neurites in the presence of a constant EF (DC). A similar behavior was observed in myoblasts [30], where these were aligned perpendicular to the applied EF.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, treadmill exercise transiently increases muscle (33) and bone BF (34) in nonneurologically impaired models. However, it is unknown whether ABPT alters bone perfusion after SCI (26,27) or improves bone recovery in paralyzed limbs (10). For example, two studies that used near-infrared spectroscopy to evaluate bone BF in persons with SCI reported no change in proximal tibia perfusion immediately after exercise in response to facilitated plantar flexor exercise (26) or functional electrical stimulation rowing (27), whereas increased bone BF was present in nonneurologically impaired controls.…”
Section: Discussionmentioning
confidence: 99%
“…Activity-based physical therapy (ABPT) modalities that mobilize and/or reload the paralyzed limbs (e.g., bodyweight-supported treadmill training (BWSTT) or passive limb movements) increase BF in the impaired extremities (6)(7)(8) and may improve muscle recovery (9). Various ABPT regimens have also been promoted as a means to increase BMD after SCI (10), as intermittent loading with high peak strains or high strain rates increases BMD in neurologically intact persons (11). However, well-controlled trials evaluating the influence of ABPT on BMD in persons with SCI have produced inconsistent results, especially when assessing the distal femur and proximal tibia sites that are most prone to fracture in this population (10).…”
mentioning
confidence: 99%
“…Sclerostin is a biomarker of SCI-induced OP, playing an important role in mediating bone loss in response to unloading ( 60 ). Canonical Wnt signaling promoted bone formation by stimulating osteoblast differentiation and osteoblast growth ( 61 ). For example, several proteins involved in Wnt signaling were repressed in the distal femur and proximal tibia after SCI, while the number of osteocytes stained for Sclerostin was increased ( 62 ), which contributed to the occurrence of OP.…”
Section: Discussionmentioning
confidence: 99%